Management of water resources to control groundwater levels in the southern area of the western Nile delta, Egypt - El-Arabib, N.E. (2020)
The present study was initiated with the objective of simulating and predicting the effect of future development on the groundwater flow and levels. The study area extends south of El Nubariya canal including Sadat City area and its vicinities in the western Nile delta region. A numerical groundwater flow model (MODFLOW) has been employed to simulate flow and get the budget of groundwater in the study area. The model showed that about 28,101,041 m3/day of surface water is infiltrated to groundwater dominantly from canals and excess irrigation water. About the same quantity (28,101,052 m3/day), is discharged from groundwater through production wells, open drains and through some reaches of canals. Three development scenarios were simulated to give predictions of the impact of future increasing recharge, construction of new canal and new open drains, and also increased pumping on the groundwater levels in the study area.